KARAKTERISTIK LINGKUNGAN PERAIRAN SELAT RUPAT - Syahril Nedi; Bambang Pramudya; Etty Riani; Manuwoto Manuwoto (Program Pascasarjana Universitas Riau, 2010)
Rupat Strait is one of small strait in Malacca Strait which located in among coastal of TownDumai area with the Rupat Island in Riau Province. Position of Rupat Strait semi-closed withthe condition of semi-diurnal tide has potency to cause the happening of oil accumulation interritorial water which can generate the damage of ecosystem territorial waters. Strait Rupatown the variety of various type mangrove representing habitat of various fish type and protectthe coast from wave and aberration. Various transportation activity, processing and oildistribution in coastal area of Dumai cause the territorial water of Strait of Rupat gristle to oilcontamination. Lubuk Gaung is a very sensitive regional to oil contamination. Pulau Ketam is asensitive criteria, but region Pelintung is inclusive of middle criteria untill is not sensitivity.